Зародження правового регулювання діяльності європейських кооперативних організацій у XIX - на початку XX ст. - Волошкевич, Г. А.; Voloshkevich, G. (My University, 2010)
The article investigates legal background of societies in Europe in the 19th – the beginning of 20th centuries. It considers the policy of tsarist government in the ﬁ eld of cooperative building and legislation, legal support of the functioning of societies, legal aspects of interrelationships between authority representatives and cooperative organizations, the formation of basic cooperative-legal institutions in European law.
Волошкевич Г. А. Зародження правового регулювання діяльності європейських кооперативних організацій у XIX - на початку XX ст. / Г. А. Волошкевич // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 525-531.
Keywords: правове регулювання діяльності європейських кооперативних організацій; кооперативне законодавство у європейських країнах; державна політика в сфері кооперативного руху; становлення кооперативно-правових інститутів у європейському праві; правовое регулирование деятельности европейских кооперативных организаций; кооперативное законодательство в европейских странах; государственная политика в сфере кооперативного движения; становление кооперативно-правовых институтов в европейском праве; legal regulation of the activities of European co-operative organizations; cooperative legislation in Europe; State policy in the field of the cooperative movement; the establishment of cooperative and legal institutions in European law